Towards Green Ammonia Synthesis through Plasma‐Driven Nitrogen Oxidation and Catalytic Reduction - Hollevoet, Lander; Jardali, Fatme; Gorbanev, Yury; Creel, James; Bogaerts, Annemie; Martens, Johan A. (Angewandte Chemie International Edition, 2020)
Ammonia is an industrial large‐volume chemical, with its main application in fertilizer production. It also attracts increasing attention as a green‐energy vector. Over the past century, ammonia production has been dominated by the Haber–Bosch process, in which a mixture of nitrogen and hydrogen gas is converted to ammonia at high temperatures and pressures. Haber–Bosch processes with natural gas as the source of hydrogen are responsible for a significant share of the global CO2 emissions. Processes involving plasma are currently being investigated as an alternative for decentralized ammonia production powered by renewable energy sources. In this work, we present the PNOCRA process (plasma nitrogen oxidation and catalytic reduction to ammonia), combining plasma‐assisted nitrogen oxidation and lean NOx trap technology, adopted from diesel‐engine exhaust gas aftertreatment technology. PNOCRA achieves an energy requirement of 4.6 MJ mol−1 NH3, which is more than four times less than the state‐of‐the‐art plasma‐enabled ammonia synthesis from N2 and H2 with reasonable yield (>1 %). The PNOCRA (non‐thermal plasma nitrogen oxidation and catalytic reduction to ammonia) process allows decentralized ammonia production from water, air and renewable energy through nitrogen oxidation and subsequent catalytic reduction in a lean NOx trap (LNT). The related energy cost of 4.61 MJ mol−1 NH3 is more than four times less than the current best available technology for plasma‐based ammonia production.